Hippocampal LASP1 ameliorates chronic stress-mediated behavioral responses in a mouse model of unpredictable chronic mild stress. (15th February 2021) - Cui, Yan-Hui; Fu, Ao; Wang, Xue-Qin; Tu, Bo-Xuan; Chen, Kang-Zhi; Wang, Yi-Kai; Hu, Qiong-Gui; Wang, Lai-Fa; Hu, Zhao-Lan; Pan, Pin-Hua; Li, Fang; Bi, Fang-Fang; et al.
Abstract: Substantial evidence has revealed that abnormalities in synaptic plasticity play important roles during the process of depression. LASP1 (LIM and SH3 domain protein 1), a member of actin-binding proteins, has been shown to be associated with the regulation of synaptic plasticity. However, the role of LASP1 in the regulation of mood is still unclear. Here, using an unpredictable chronic mild stress (UCMS) paradigm, we found that the mRNA and protein levels of LASP1 were decreased in the hippocampus of stressed mice and that UCMS-induced down-regulation of LASP1 was abolished by chronic administration of fluoxetine. Adenosine-associated virus-mediated hippocampal LASP1 overexpression alleviated the UCMS-induced behavioral results of forced swimming test and sucrose preference test in stressed mice. It also restored the dendritic spine density, elevated the levels of AKT (a serine/threonine protein kinase), phosphorylated-AKT, insulin-like growth factor 2, and postsynaptic density protein 95. These findings suggest that LASP1 alleviates UCMS-provoked behavioral defects, which may be mediated by an enhanced dendritic spine density and more activated AKT-dependent LASP1 signaling, pointing to the antidepressant role of LASP1. Highlights: UCMS down-regulated LASP1 expression in the hippocampus of mice. Hippocampal LASP1 overexpression attenuated the defected behavioral responses induced by UCMS. Hippocampal LASP1 overexpression restored the dendritic spine density, and elevated the levels of p-AKT, IGF2, as well as PSD95.